2019
DOI: 10.1108/fs-05-2019-0040
|View full text |Cite
|
Sign up to set email alerts
|

Foresight for stock market volatility – a study in the Indian perspective

Abstract: Purpose Volatility is a permanent behavior of the stock market around the globe. The presence of the volatility in the stock price makes it possible to earn abnormal profits by risk seeking investors and creates hesitancy among risk averse investors as high volatility means high return with high risk. Investors always consider market volatility before making any investment decisions. Random fluctuations are termed as volatility of stock market. Volatility in financial markets is reflected because of uncertaint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…Volatilitas harga saham adalah variasi perubahan harga saham yang ditandai dengan jarak antara naik dan turunnya harga saham pada periode waktu tertentu (Nurhaliza, 2021). Menurut Dixit & Agrawal (2020) volatilitas adalah hal yang lumrah di lantai bursa saham karena volatilitas harga saham adalah salah satu hal yang dipertimbangkan oleh investor sebelum mereka mengambil keputusan investasi. Bagi para investor konservatif yang takut untuk mengambil risiko, mereka akan menghindari investasi jika harga saham sedang fluktuatif karena menganggap volatilitas yang tinggi menciptakan ketidakpastian dan tidak mewakili nilai intrinsik saham yang sebenarnya.…”
Section: Kajian Teoriunclassified
“…Volatilitas harga saham adalah variasi perubahan harga saham yang ditandai dengan jarak antara naik dan turunnya harga saham pada periode waktu tertentu (Nurhaliza, 2021). Menurut Dixit & Agrawal (2020) volatilitas adalah hal yang lumrah di lantai bursa saham karena volatilitas harga saham adalah salah satu hal yang dipertimbangkan oleh investor sebelum mereka mengambil keputusan investasi. Bagi para investor konservatif yang takut untuk mengambil risiko, mereka akan menghindari investasi jika harga saham sedang fluktuatif karena menganggap volatilitas yang tinggi menciptakan ketidakpastian dan tidak mewakili nilai intrinsik saham yang sebenarnya.…”
Section: Kajian Teoriunclassified
“…Some authors found PGARCH model to best fit the data from Indian stock market amongst all the models evaluated from the GARCH family (Dixit & Agrawal, 2019). Akigray (Akgiray, 1989) found GARCH(1,1) to be most suitable for modelling daily returns on CRSP indices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When using GARCH family models to analyse and forecast return volatility, the selection of input variables for forecasting is paramount, as essential conditions will be given for the method to have a stationary solution and perfect matching (Nelson 1990). Dixit and Agrawal (2019) also suggested that the P-GARCH model is the most suitable to predict and forecast stock market volatility for the Bombay Stock Exchange (BSE) and National Stock Exchange (NSE) of India. The authors also highlighted the fact that volatility in financial markets is reflected because of uncertainty in the price, return, unexpected events and non-constant variance, which can be measured through the GARCH models that will give insight for investment decisions.…”
Section: Literature Reviewmentioning
confidence: 99%